PENGARUH FLASH SALE DAN TAGLINE GRATIS ONGKIR SHOPEE TERHADAP PEMBELIAN IMFULSIF DI BENGKULU - Oki Syahputra; Zelin Wahyuni; Meilaty Finthariasari (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
Research was conducted on Shopee Marketplace users in Bengkulu City. The aim of this research is to find out the influence of flash sales and free shipping taglines on impulse purchases on the Shopee marketplace in Bengkulu City, both partially and simultaneously. Sampling in this research used a purposive sampling method and used 110 respondents as research samples. The types of data used are primary and secondary data. Primary data is obtained through distributing questionnaires directly to respondents, and secondary data sources support information from primary data, such as literature studies, previous researchers, and data obtained via the internet (online). The data analysis techniques used are research instrument tests, classical assumption tests, multiple linear regression analysis, determinant coefficient tests (R2)) and hypothesis tests, namely the t test and f test. The research results show that flash sales and free shipping taglines influence impulse purchases. The R Square value was obtained at 0.210 , or equal to 21.0% , which shows that the flash sale and free shipping tagline can explain and provide the information needed to predict the impulse buying variable of 21.0%. Meanwhile, the remaining 79.0% was influenced by other variables not examined in the research. Kata Kunci : Flash Sale, Tagline Gratis Ongkir, Pembelian Impulsif.